2009
DOI: 10.1097/ncq.0b013e31818f528e
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Serious Injury From Falls in Two Veterans' Hospital Medical-Surgical Units

Abstract: A large veteran's hospital participated in a year-long collaborative project across 9 hospitals to reduce serious injury from falls in acute care, targeting medical-surgical units. The primary objective of this project was to develop and test a set of interventions (bundles) to prevent serious physical injury (fractures and hemorrhagic bleeds) from patient falls. The interventions were implemented using tests of change on 2 medical-surgical units focused on engaging unit-based staff and combining innovations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 11 publications
2
71
0
Order By: Relevance
“…Nurses should assess each patient's risk factors, including fall-related perceptions, and then integrate information on specific risk factors into a fall-prevention plan. [53][54][55][56][57] Nurses can tailor communication about falls to fit a patient's perceptions and use the teach-back method to determine how much and how well the patient comprehends and recalls what the nurse told them. 56,57 Because research 52 suggests that inpatients may not call for help for fear of losing their independence, nurses can emphasize the temporary nature of the activity restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses should assess each patient's risk factors, including fall-related perceptions, and then integrate information on specific risk factors into a fall-prevention plan. [53][54][55][56][57] Nurses can tailor communication about falls to fit a patient's perceptions and use the teach-back method to determine how much and how well the patient comprehends and recalls what the nurse told them. 56,57 Because research 52 suggests that inpatients may not call for help for fear of losing their independence, nurses can emphasize the temporary nature of the activity restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…For the most part, study participants identified numerous low-or no-cost solutions to address risk factors and failures identified in the model. In a 1 yr learning collaborative involving nine hospitals, Quigley et al successfully tested a bundle of interventions on medical-surgical and mental health units to prevent falls and, thus, serious injuries [47][48][49]. One year following this multisite quality improvement project, the sustainability of the collaborative was evaluated and the collaborative was found to have positive outcomes [50].…”
Section: Behaviormentioning
confidence: 99%
“…Evidence of effective teaching of patients would be the patient who can "teach back"-that is, tell and show you back correctly and consistently. 11 These principles of patient education are not new to ICU nurses but may require redesign of care delivery so that patient education for fall and injury prevention emerges as a priority in care management. Although a patient may not fall in the critical care unit, nurses are influential in patients' continued safety while the patients are in the hospital and after discharge.…”
Section: Diagnosismentioning
confidence: 99%
“…Injury risk assessment is a separate practice from fall risk assessment and focuses on identifying the presence of "ABCS" factors (Age, >85 years; Bones, osteoporosis diagnosis or treatment, history of fracture, especially hip fracture; Coagulation, anticoagulant therapy; Surgery, recent major abdominal, thoracic, or lower extremity). 11 Handoff communication should include initial assessment and any changes to fall and injury risk on future handoff. Critical care nurses' assessments are often the first safety assessments before those of interdisciplinary team members.…”
Section: Outcomes Managementmentioning
confidence: 99%
See 1 more Smart Citation